Flak on the Frontline: How dissent was suppressed in early-neoliberal Aotearoa - Watts, Barnaby (New Zealand Sociology, 2026)
In April 1990, an episode of the Television New Zealand current affairs programme Frontline which criticised the fourth Labour government's close relationship with big business became the centre of an extraordinary scandal. Its makers were the target of fierce flak, as TVNZ was sued by the incumbent Prime Minister and three other Cabinet ministers, whilst the Broadcasting Standards Authority upheld complaints made by the Treasury and the New Zealand Business Roundtable. This article considers this episode to be a critical and overlooked flashpoint in the history of neoliberalism in Aotearoa, as it demonstrates how contestation in the media was a crucial ideological dimension of class struggle during the inception of the neoliberal regime. Using a Marxist and political economic theoretical framework, this article details how the early proponents of neoliberal reform marginalised dissent. It also outlines how a Marxist approach is needed in order to produce a more systematic critique of government-business relations, as the programme’s relatively unsophisticated analysis made it an easier target for the backlash it received.